Greetings from Trinidad, B.W.I. - Thomas, H.O. (H.O. Thomas, Trinidad, 2009)
Description on the back of the postcard reads: "Greetings From Trinidad, B.W.I. Bathers relax at popular Coral "Beach Club" while bauxite carrier in the background unload at Tembladore". The postcard is addressed to Miss H.F. Riley, Mass, U.S.A. The postcard is date January 17, 1958 and numbered 23962.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bauxite--Trinidad and Tobago; 1958; Ships--Trinidad and Tobago; Clubs--Trinidad and Tobago